Assessment of Genetic Variability for Agroeconomic Traits in Green Gram: GENETIC VARIABILITY IN GREEN GRAM - Devendra Chandel; Sundar Anchra; Anil Kumar; Ravindra Kumar; Hukam Singh Kothyari; N. K. Sharma (Annals of Arid Zone, 2024)
Eighty three genotypes of mung bean were assessed for genetic variability and agro-economic traits during summer-2018. These genotypes exhibited significant differences for all the 11 characters studied. Six genotypes namely ML-818, Keshwanand Mung-1, GM-4, MH-2-15, IPM 02-3 and COGG-912 were identified to possess the desirable traits. Highest values of GCV and PCV was recorded for number of branches per plant whereas their lowest values were recorded for pod length, number of seeds per pod and days to maturity. A high degree of genetic variability along with high heritability and high genetic advance as percentage of mean were recorded for days to 50% flowering, number of pods per plant, 100-seed weight and biological yield per plant. This indicates that these characters are controlled by additive gene action and can therefore serve as a basis for selection in improvement programs. The presence of ample genetic diversity in the germplasm suggests that these varieties can be used in recombination breeding programs to develop high yielding varieties for the arid zone.